O Mediterrâneo de Braudel - Arruda, José Jobson de Andrade (Anais do Museu Paulista: História e Cultura Material, 1984)
This paper deals with Fernand Braudel's classical book, O Mediterrâneo na Época de Filipe II. It retrieves the historical context in which it was written and reframes its main methodological proposal based on the notion of short-, médium-, and long-term duration: the dialectics of duration as opposed to the dialectis of social relations.